Effect of different anesthesia techniques on the serum brain-derived neurotrophic factor (BDNF) levels - Ozer, A. B.; Demirel, I.; Erhan, O. L.; Firdolas, F.; Ustundag, B. (Verduci Publisher, 2015)
OBJECTIVE: Serum Brain-Derived Neurotrophic Factor (BDNF) levels are associated with neurotransmission and cognitive functions. The goal of this study was to examine the effect of general anesthesia on BDNF levels. It was also to reveal whether this effect had a relationship with the surgical stress response or not. PATIENTS AND METHODS: The study included 50 male patients, age 20-40, who were scheduled to have inguinoscrotal surgery, and who were in the ASA I-II risk group. The patients were divided into two groups according to the anesthesia techniques used: general (GA) and spinal (SA). In order to measure serum BDNF, cortisol, insulin and glucose levels, blood samples were taken at four different times: before and after anesthesia, end of the surgery, and before transferal from the recovery room. RESULTS: Serum BDNF levels were significantly low (p < 0.01), cortisol and glucose levels were higher (p < 0.05 and p < 0.01) in Group GA compared with Group SA. No significant difference was detected between the groups in terms of serum insulin levels. There was no correlation between serum BDNF and the stress hormones. CONCLUSIONS: Our findings suggested that general anesthetics had an effect on serum BDNF levels independent of the stress response. In future, BDNF could be used as biochemical parameters of anesthesia levels, but studies with a greater scope should be carried out to present the relationship between anesthesia and neurotrophins.
Keywords: BDNF; General anesthesia; Spinal anesthesia; Stress response